2021
DOI: 10.3171/case21338
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy and carotid artery stenting for stenosis of the internal carotid artery with free-floating thrombosis: illustrative case

Abstract: BACKGROUND The authors report a case in which mechanical thrombectomy and carotid artery stenting (CAS) were performed for acute cerebral infarction with free-floating thrombosis (FFT) in left internal carotid artery (ICA) stenosis. Good results were obtained. OBSERVATIONS A 63-year-old man developed sudden disturbance of consciousness and right hemiplegia. He was transported to the authors’ hospital by an emergency vehicle. Head magnetic resonance imaging showed acute cerebral infarction in the left middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
“…Although these reports have not demonstrated a standardized technique for the mechanical thrombectomy of CFFTs, numerous methods including stentrievers, reversal of carotid flow with occlusion balloons, and distal filter wire placement have been reported. [6][7][8][9][10][11][12][13][14][15][16][17] Recently, direct aspiration, with or without the utilization of proximal and distal protection devices have been described. 11,20,27 To harness all the benefits of previously reported techniques we employed a triple stentriever "bouquet" technique for the mechanical thrombectomy of a CFFT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in addition to conventional treatments, endovascular thrombectomy for carotid FFT has been reported [2,4,5,[7][8][9][10][11][12][13][14]. However, when balloon protection is used for distal protection, complete interruption of the ICA flow is undesirable in patients without hemodynamic intolerance.…”
Section: Discussionmentioning
confidence: 99%